Perancangan Interior Restoran Bandar Djakarta di Surabaya - Noviana Angelina Hiu; mariana wibowo (Intra, 2016)
Many seafood restaurants opened in every corner of the city of Surabaya due to high demand of seafood in this city, but the existing seafood restaurants provide less information about seafood they sell. Consequently, many seafood enthusiasts who just ordered a seafood menu that they know without daring to try other seafood species. Interior Design Restaurant Bandar Djakarta in Surabaya aims to create restaurants that provide comfort, a different atmosphere and informative for consumers while still maintaining the image or the image of the restaurant Bandar Djakarta itself. To achieve the goals and answer the problems are then given the concept of the indoor garden is informative yet retain a characteristic of Bandar Djakarta itself. This was achieved by using a design concept that characterizes the city Djakarta garden seafood that is applied to the interior elements of both walls, floor, ceiling, furniture and other decorative elements. Informative value provided to consumers aiming to provide more knowledge to consumers menengenai seafood sold in restaurants Bandar Djakarta. Mation is expected to know the information provided, the consumer better understand and know what they are eating and the benefits obtained